Comparative study of the mating process for a spar-type floating wind turbine using two alternative installation vessels. (March 2023) - Liu, Ting; Halse, Karl H.; Leira, Bernt J.; Jiang, Zhiyu
Abstract: The offshore wind industry faces many challenges as the water depth of offshore sites increases. For installation of the spar floating offshore wind turbines (OWTs), cost-effective installation methods are needed to facilitate installations at moderate or deep-water depths. In this paper, a novel installation concept initially designed for installing pre-assembled wind turbines is further studied. Two alternative installation vessels (i.e., a catamaran and a small water-plane area twin hull vessel (SWATH)) equipped with a dynamic positioning (DP) system are considered for installing 10-MW OWTs. Hydrodynamic responses of the installation systems are obtained by the fully coupled nonlinear time domain method. Based on the numerical analysis in SIMO-Riflex, a comparative study of the two vessel concepts is conducted to study selected response variables of two mating points. Compared with the catamaran installation vessel, the SWATH substantially reduces dynamic motions during the critical mating phase. The findings of this paper provide references for industrial stakeholders selecting alternative installation vessels and serve as a basis for further optimizing the concept.